Impossible Joyce : Finnegans wakes - O'Neill, Patrick, 1945- (Toronto, ON, Canada : University of Toronto Press, 2013)
James Joyce's Finnegans Wake has repeatedly been declared to be entirely untranslatable. Nonetheless, it has been translated, transposed, or transcreated into a surprising variety of languages - including complete renditions in French, German
Work in progress -- Words in progress -- Rivering waters -- Naming names.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941 -- Translations -- History and criticism; Joyce, James, -- 1882-1941; Joyce, James, -- 1882-1941 -- Traductions -- Histoire et critique; Joyce, James, -- 1882-1941; Finnegans wake (Joyce, James); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Translations; Criticism, interpretation, etc